Differences in the chemical composition of organic‐walled dinoflagellate resting cysts from phototrophic and heterotrophic dinoflagellates. Issue 2 (15th March 2014) - Bogus, Kara; Mertens, Kenneth Neil; Lauwaert, Johan; Harding, Ian C.; Vrielinck, Henk; Zonneveld, Karin A. F.; Versteegh, Gerard J. M.; Lin, S.
<x xml:space="preserve">Abstract</x> Dinoflagellates constitute a large proportion of the planktonic biomass from marine to freshwater environments. Some species produce a preservable organic‐walled resting cyst (dinocyst) during the sexual phase of their life cycle that is an important link between the organisms, the environment in which their parent motile theca grew, and the sedimentary record. Despite their abundance and widespread usage as proxy indicators for environmental conditions, there is a lack of knowledge regarding the dinocyst wall chemical composition. It is likely that numerous factors, including phylogeny and life strategy, determine the cyst wall chemistry. However, the extent to which this composition varies based on inherent (phylogenetic) or variable (ecological) factors has not been studied. To address this, we used micro‐Fourier transform infrared spectroscopy to analyze nine cyst species produced by either phototrophic or heterotrophic dinoflagellates from the extant orders Gonyaulacales, Gymnodiniales, and Peridiniales. Based on the presence of characteristic functional groups, two significantly different cyst wall compositions are observed that correspond to the dinoflagellate's nutritional strategy. The dinocyst wall compositions analyzed appeared carbohydrate‐based, but the cyst wall produced by phototrophic dinoflagellates suggested a cellulose‐like glucan, while heterotrophic forms produced a nitrogen‐rich glycan. This constitutes the first empirical evidence nutritional strategy is related to different dinocyst wall chemistries. Our results indicated phylogeny was less important for predicting composition than the nutritional strategy of the dinoflagellate, suggesting potential for cyst wall chemistry to infer past nutritional strategies of extinct taxa preserved in the sedimentary record.